Bone Mineral Density Changes Among Young, Healthy African Women Receiving Oral Tenofovir for HIV Preexposure Prophylaxis. (1st March 2016) - Mirembe, Brenda G.; Kelly, Clifton W.; Mgodi, Nyaradzo; Greenspan, Susan; Dai, James Y.; Mayo, Ashley; Piper, Jeanna; Akello, Carolyne A.; Kiweewa, Flavia M.; Magure, Tsitsi; Nakabiito, Clemensia; Marrazzo, Jeanne M.; et al.
Abstract : Background: Limited data exist on effect of tenofovir disoproxil fumarate (TDF) when used for preexposure prophylaxis (PrEP) on bone mineral density (BMD) in HIV-negative women. We evaluated the effect of daily oral TDF and emtricitabine/TDF compared with placebo on BMD among women enrolled in an HIV-1 PrEP trial. Methods: HIV-uninfected women in Uganda and Zimbabwe had BMD measurements of lumbar spine (LS) and total hip (TH) by dual-energy x-ray absorptiometry at baseline and every 24 weeks for 48 weeks of active treatment and for 48 weeks after discontinuation of study medication. Plasma tenofovir levels were assessed every 12 weeks for the first 48 weeks. Results: Of 518 women enrolled, 432 had dual-energy x-ray absorptiometry results at baseline and week 48. In the primary analysis, no significant differences in percent BMD change in hip or spine between arms observed, likely because of low product adherence. Among the subset with tenofovir detection in 75%–100% of plasma samples, the mean percent BMD change from baseline to week 48 in the LS was 1.4% lower for TDF or emtricitabine/TDF recipients than for placebo ( P = 0.002) and TH BMD was 0.9% lower ( P = 0.018). BMD changes from end of active treatment to 48 weeks were significantly greater in the active arm participants compared with placebo participants with a net difference of approximately +0.9% at the LS ( P = 0.007) and +0.7% ( P = 0.003) at the TH. Conclusions: TDF-containing oral PrEP resulted in small but significant reversible decreases in hip and spine BMD among young African women.